Factors associated with nonalcoholic fatty liver disease grades detected by ultrasound at a screening center in Klang Valley, Malaysia - Khammas, Abdul Sattar Arif; Mohammed, Sayed Safwan; Abu Hassan, Hasyma; Kadir @ Shahar, Hayati; Mohamad Ibrahim, Ramlah; Mohd Nasir, Nurul Nadiah; M. Salih, Sarah Qahtan; Mahmud, Rozi (Faculty of Medicine University of Baghdad, 2018)
Background: Non-alcoholic fatty liver disease (NAFLD) is a very common liver disease in the world, particularly in Western and developed countries. It is rapidly growing in the Asia- Pacific region. Objectives: This study was designed to determine the association between risk factors and non-alcoholic fatty liver disease grades among Malaysian adults. Patients and Methods: A cross-sectional observational study design was prospectively carried out in this study. Consecutive 628 respondents who attended for a medical checkup at urban health center had been recruited for the study. All respondents had the physical examination, blood tests, clinical assessments, and abdominal ultrasound. A structured self-administered questionnaire has been also used in this study in this survey. Results: From a total of 628 “health screened” subjects, 235 subjects (37.4%) were diagnosed to have non-alcoholic fatty liver disease. Female gender and Chinese race were predominant in our study population. Of those with NAFLD, more than half subjects (63.4) had a moderate grade of non-alcoholic fatty liver disease. The mean age of the study population was 54.54 ±6.69 years. Differences of the mean body mass index (BMI) and waist to hip ratio (WHR) were found to be significant among non-alcoholic fatty liver disease grades (P< 0.001). Similarly, mean triglycerides (TG) and high-densiy lipoprotein-cholesterol (HDL-C) levels had significant differences among non-alcoholic fatty liver disease grades (P< 0.001 and P= 0.016, respectively). Conclusion: the non-alcoholic fatty liver disease is common among urban Malaysian adult population. Anthropometric measurements were closely correlated with non-alcoholic fatty liver disease grades.